Application of medicinal properties of blueberries (Vaccinium myrtillus) - Zanna Bialoszycka; Monika Białoszycka; Alisa Pachevska; Valerij Istoshyn; Alina Biloshytska (Journal of Education, Health and Sport)
Introduction: The blueberry (Vaccinium myrtillus) is a fruit that is widely consumed and is harvested from mid-June to late July. Blueberries have traditionally been recognised not only for their palatability but also as a source of medicinal raw materials in folk medicine. The use of blueberry berries and leaves as a therapeutic agent dates back to the 16th century, with applications in the treatment of various ailments, including diarrhoea, inflammation of the mouth and throat, poor circulation and vision disorders.